(untitled) (Advances in Applied Mathematics and Mechanics, 2018)
We consider a distributed optimal control problem governed by an elliptic PDE, and propose an embedded discontinuous Galerkin (EDG) method to approximate the solution. We derive optimal a priori error estimates for the state, dual state, and the optimal control, and suboptimal estimates for the fluxes. We present numerical experiments to confirm our theoretical results.